2017
DOI: 10.1186/s13019-017-0603-7
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump sutureless repair for ischemic left ventricular free wall rupture: a systematic review

Abstract: BackgroundClinical results of ischemic left ventricular free-wall rupture show high mortality rates.MethodsWe reviewed studies published after 1993 on PubMed.ResultsA sutureless technique using fibrin glue sheets or patches with/without fibrin glue might contribute to improved clinical results. However, some technique limitations remain for blowout-type ruptures, and the possibility of a pseudoaneurysm formation at the repair site after surgery should be considered.ConclusionsThe sutureless technique can be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“… 3 , 5 – 8 It is reported as occurring more often after the first transmural MI. 1 , 9 , 10 The average time from symptom onset to hospital admission in this study population was 24 hours, with a maximum onset of 94 hours. 9 Although the time from AMI to LVFWR diagnosis is usually several days, there is no clear correlation between mortality and the length of this delay.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“… 3 , 5 – 8 It is reported as occurring more often after the first transmural MI. 1 , 9 , 10 The average time from symptom onset to hospital admission in this study population was 24 hours, with a maximum onset of 94 hours. 9 Although the time from AMI to LVFWR diagnosis is usually several days, there is no clear correlation between mortality and the length of this delay.…”
Section: Discussionmentioning
confidence: 90%
“…Cardiac rupture after acute myocardial infarction (AMI), which includes ventricular free wall rupture (VFWR), septal rupture, and papillary muscle rupture, can result in lethal complications. 1 These life-threatening complications mainly occur within 7 days after MI. Left VFWR (LVFWR) is a rare but catastrophic mechanical complication that can occur after AMI and is associated with high mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of off-pump sutureless repair of LV free wall rupture concluded that off-pump sutureless patch repair of the defect can be performed with fibrin glue sheets or patches and collagen-based sponge adjuncts which are used to conform to the native myocardial tissue and provide haemostasis [ 20 ]. Furthermore, the late complication of pseudo aneurysm formation must be considered in patients for whom sutureless patch repair is performed [ 20 ]. The use of fibrin sheets or pericardial patches on the rupture site under stable haemodynamic conditions can be done on a beating heart on or off pump.…”
Section: Discussionmentioning
confidence: 99%
“…Лечение разрыва миокарда заключается в экстренном хирургическом вмешательстве. В данное время существует множество подходов к хирургическому лечению разрыва миокарда [5]. Однако иногда по разным причинам не удается провести хирургическое лечение.…”
Section: Discussionunclassified